2020
DOI: 10.1016/j.trf.2020.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Cyclists’ intentions to yield for automated cars at intersections when they have right of way: Results of an experiment using high-quality video animations

Abstract: What will cyclists do in future conflict situations with automated cars at intersections when the cyclist has the right of way? In order to explore this, short high-quality animation videos of conflicts between a car and a cyclist at five different intersections were developed. These videos were 'shot' from the perspective of the cyclist and ended when a collision was imminent should the car or the bicyclist not slow down. After each video participants indicated whether they would slow down or continue cycling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…This provides theoretical basis for hypothesising the mediated effects of perceived risk level (H4a and H4b) and perceived priority (H5a and H5b) on behavioural intention through attitude, which have been built into the developed model. However, some empirical studies directly related perceived risk level (Twisk et al, 2015) and perceived priority (Vlakveld et al, 2020) with behavioural intention. This suggests that there might be unmediated effects from perceived risk level and perceived priority to behavioural intention.…”
Section: Alternative Models For All Four Casesmentioning
confidence: 99%
“…This provides theoretical basis for hypothesising the mediated effects of perceived risk level (H4a and H4b) and perceived priority (H5a and H5b) on behavioural intention through attitude, which have been built into the developed model. However, some empirical studies directly related perceived risk level (Twisk et al, 2015) and perceived priority (Vlakveld et al, 2020) with behavioural intention. This suggests that there might be unmediated effects from perceived risk level and perceived priority to behavioural intention.…”
Section: Alternative Models For All Four Casesmentioning
confidence: 99%
“…Together, our findings suggest that eHMIs should be omnidirectional if they are to be applied in traffic scenarios where cars can approach from multiple directions. Vlakveld et al [26] showed animations of cars with an omnidirectional eHMI on the roof, whereas drive.ai [27] used multiple displays on the car's exterior. Another solution to ensure visibility from all sides is to use a light emitting diode (LED) strip as in Cefkin et al [39], or LED patterns on the lateral surfaces of the car [40].…”
Section: Performancementioning
confidence: 99%
“…What our study shows is that people look at different sides and features of the car (front, side, rear, wheels), as well as humans in cars. This, in turn, would require that eHMIs are omnidirectionally visible, for example by means of a display on the roof (Vlakveld, Van der Kint, & Hagenzieker, 2020) or LED strips on the car (Cefkin et al, 2019;Nissan, 2015;Volvo Cars, 2018). Our findings also suggest that an eHMI on only the front of the car, which appears to be the norm in the literature so far , is of limited use in parking garages, as the fronts of cars receive less than 50% of the attention than the backs of cars.…”
Section: Discussionmentioning
confidence: 99%